Das Johannesevangelium und die antike griechische Philosophie : Untersuchung des philosophischen Hintergrunds der langen Reden Jesu im JohEv Band I (Joh 1-12) - Despotis, Athanasios, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This monograph offers a detailed commentary on Jesus's long speeches in John 1-12, revealing how the Gospel of John engages with the religious and philosophical discourses of its time. By examining these speeches, the study uncovers how John creates new syntheses, integrating sophisticated grammatical and rhetorical features. It also explores the ancient patristic exegesis, ensuring a nuanced understanding of the historical and cultural context of the New Testament. This work provides fresh insights into the intersection of philosophy, rhetoric, and theology in the Johannine corpus. Diese Monographie bietet einen detaillierten Kommentar zu den langen Reden Jesu in Johannes 1-12 und zeigt auf, wie das Johannesevangelium mit den religiösen und philosophischen Diskursen seiner Zeit interagiert. Durch die Untersuchung dieser Reden wird ersichtlich, wie Johannes neue Synthesen schafft und dabei anspruchsvolle grammatische und rhetorische Elemente integriert. Sie beleuchtet auch die antike patristische Exegese, um eine differenzierte Wahrnehmung des historischen und kulturellen Kontextes des Neuen Testaments zu gewährleisten. Diese Arbeit liefert neue Einsichten in die Schnittstelle von Philosophie, Rhetorik und Theologie im johanneischen Corpus.